Dialogues concerning natural religion and other writings - Hume, David (Cambridge University, 2013)
David Hume's Dialogues concerning Natural Religion, first published in 1779, is one of the most influential works in the philosophy of religion and the most artful instance of philosophical dialogue since the dialogues of Plato. It presents a fictional conversation between a skeptic, an orthodox Christian, and a Newtonian theist concerning evidence for the existence of an intelligent cause of nature based on observable features of the world. This new edition presents it together with several of Hume's other, shorter writings about religion, and with brief selections from the work of Pierre Bayle, who influenced both Hume's views on religion and the dialectical style of the Dialogues. The volume is completed by an introduction which sets the Dialogues in its philosophical and historical contexts.